UJI PERANGKAT LUNAK ELECTRONIC SMART CODE ICD-10 (KODE Z) PADA KODEFIKASI DIAGNOSIS PASIEN DENGAN METODE MEASURING EFFORT, DAN PROBABILITAS PERBAIKAN DARI NILAI CFP - trisnanto, puguh yudho; Djuwadi, Ganif; Candra, Adil (DINAMIKA DOTCOM, 2017)
Electronic smart code icd-10 (code z) on the diagnosis of patient diagnosis in contact with health service at cisadea urban poor health center was tested by RCAF using fourteen subject module value by yielding the value of subject 34 that was connected using CFP / degree of complexity With value of CFP 70 so as to produce value FP 69,3 result of FP is done by analysis of PL level by using Measuring Effort Test (Business Measurement) which yield value 10,24 after done Schedule and Staff test so as to produce Standard Value of Cyclomatic Complexity 10 (Structured Procedure Well and stable and low risk) Probability test 5%. Keywords: Function Point, Measuring Effort, Electronic smart code icd-10 (z code)